PROGNOSTIC PREDICTORS OF SPECIAL TECHNICAL AND TACTICAL TRAINING OF PARALYMPIC SWIMMERS WITH LESIONS OF THE MUSCULOSKELETAL SYSTEM - Vinokurov L.V.; Mosunov D.F.; Nazarenko Yu.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify and determine the predictors of special technical and tactical training of highly qualified Paralympic swimmers in the sport of persons with lesions of the musculoskeletal system (LMS). Methods and structure of the study. When swimming highly qualified athletes with LMS using various sports methods, surface and underwater video filming of the phases of the swimming cycle was performed. 550 videos of swims at training and competitive events of athletes of the Paralympic national swimming team of the Russian Federation in swimming of the sport of people with LMS for the period 2019-2022 were analyzed. A survey was carried out (oral semi-structured interview) of coaches working with paraswimmers (from Candidate Master of Sports to Honored Master of Sports) of the sport of persons with LMS. Results and conclusions. For paraswimmers with LMS, two groups of prognostic predictors of special (hydrodynamic) technical and tactical training (TTT) were found - specific and typical predictors-deviations that reflect the subject of pedagogical influence (elimination or compensation formed in the swimming technique of a particular paraswimmer) by the coach. The main relationships of specific predictors with informative indicators of swimming technique, the manifestations of typical predictors in technique and the possibility of their correction in a Paralympic swimmer have been established and described.